A Clash of Ideals: The Introduction of Televised Information in Sweden, 1969–1972. Issue 3 (3rd July 2022) - Stjernholm, Emil
Abstract : In 1969, a government report concluded that there was a need for closer contact between the citizens and Swedish government agencies. Television, at this time still considered a new medium, was highlighted in the report as a valuable form of mass communication with great yet unfulfilled promise as a disseminator of government information. A heated debate about the role and function of government information ensued, not least within the public service broadcaster Sveriges Radio. While much research has been devoted to the Swedish public service model, little is known about Swedish television's function as a communication tool for government authorities. The article shows that the discursive struggles surrounding Swedish government agencies' use of television centered on three main issues: public service broadcasting's independence, the dangers related to one-way mass communication, and the shape and aesthetics of government information. By shedding light on the introduction of the program Anslagstavlan, this article contributes to a previously forsaken media history of televised information.